A Research Agenda for Heritage Planning Perspectives from Europe - Stegmeijer, Eva; Veldpaus, Loes (Edward Elgar Publishing, 2021)
This insightful Research Agenda examines the multidimensional relationships between heritage planning and pressing current societal challenges around climate, identity and development. Mapping future avenues for the field, it suggests new approaches to executing, studying and reflecting on heritage planning.